2021
DOI: 10.1002/joc.7289
|View full text |Cite
|
Sign up to set email alerts
|

Wind stilling‐reversal across Sweden: The impact of land‐use and large‐scale atmospheric circulation changes

Abstract: This study analyses for the first time the break in the stilling detected by previous research around 2010, with focus in Sweden using homogenized nearsurface mean and gust wind speed observations for 1997-2019. During the recent past two decades, both mean and gust wind magnitude and frequency (exceeding the 90th percentile) underwent nonlinear changes, driven by the dominant winter variability. In particular, consistent with previous studies, the significant (p < .05) stilling ceased in 2003, followed by no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…Overall, the homogenized WS series during 1925-2021 presented a stronger correlation with the North Atlantic Oscillation (NAO) than that of the raw WS series (0.54 vs 0.29). This improved relationship with NAO confirms and extends the result of Minola et al (2016) and Minola et al (2021) using the data after 1956 in Sweden. These results stress the importance of the century-long homogenized WS series in increasing our understanding of the recent WS stilling and recovery.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, the homogenized WS series during 1925-2021 presented a stronger correlation with the North Atlantic Oscillation (NAO) than that of the raw WS series (0.54 vs 0.29). This improved relationship with NAO confirms and extends the result of Minola et al (2016) and Minola et al (2021) using the data after 1956 in Sweden. These results stress the importance of the century-long homogenized WS series in increasing our understanding of the recent WS stilling and recovery.…”
Section: Discussionsupporting
confidence: 84%
“…As revealed by many previous studies (Roderick et al, 2007;Vautard et al, 2010;McVicar et al, 2012;Minola et al, 2016;Laapas and Venäläinen, 2017;Azorin-Molina et al, 2018;Zeng et al, 2019;Zhang and Wang, 2020), WS decreased from the 1970s to 2010s, and subsequently recovered over many terrestrial regions of the Northern Hemisphere -this is known as the WS stilling and recovery. Possible causes of the WS stilling and recovery have been widely discussed, and include changes in surface roughness induced by greenness and land use/cover change (Vautard et al, 2010;Wu et al, 2018a;, and large-scale atmospheric circulation changes (Azorin-Molina et al, 2018;Wu et al, 2018b;Zeng et al, 2019), such as the North Atlantic Oscillation (NAO) as revealed in Sweden by Minola et al (2016) and Minola et al (2021). However, all of the studies relied on available WS series starting in the 1950s or 1960s when the World Meteorological Organization (WMO) began to guide automatic weather monitoring in 1950 (WMO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such seasonal differences could be explained by the impact of large-scale atmospheric circulation, in particular by the in uence of the North Atlantic Oscillation, especially when it comes to modulate winter NSWS variability. In addition, Minola et al (2021) investigated NSWS changes across Sweden for the recent past two decades (i.e., 1997-2019), which were only partly covered by Minola et al (2016). Here it is shown that the stilling ceased in 2003, and no clear trend can be detected afterwards.…”
Section: Introductionmentioning
confidence: 92%
“…In fact, in a changing climate, regional warming differences control variations of regional surface pressure gradients, which modulate circulation patterns (Li et al 2013). For instance, phase changes of the North Atlantic Oscillation (Azorin-Molina et al 2018a; Minola et al 2021) and of the Paci c Decadal Oscillation (Zeng et al 2019) have been linked to the reversal in the terrestrial stilling. The aging of measuring instruments has also been suggested as a potential cause of the NSWS decrease (Azorin-Molina et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…A reversal in terrestrial stilling with a slight recovery of wind speed during the most recent decade has been documented for China (Yang et al., 2012), South Korea (Kim & Paik, 2015), Saudi Arabia (Azorin‐Molina, Rehman, et al., 2018) and Sweden (Minola et al., 2022). Zeng et al.…”
Section: Introductionmentioning
confidence: 93%